2012
DOI: 10.1002/nau.22253
|View full text |Cite
|
Sign up to set email alerts
|

Development of a differential suction electrode for improved intravaginal recordings of pelvic floor muscle activity: Reliability and motion artifact assessment

Abstract: The DSE has excellent between-trial reliability and performs better than the Femiscan™ electrode in terms of motion artifact contamination. It does not perform as well as the Femiscan™ electrode in terms of between-day reliability--a result that is not unexpected given the localized region from which the DSE records activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 12 publications
(16 reference statements)
1
15
0
Order By: Relevance
“…Hodges et al 38 reported that crosstalk was not a problem when recording EMG activation from the PFMs using the Periform probe as long as contractions performed by the hip musculature were relatively low amplitude, although they used data from only one participant, hip external rotation was not tested, and the methods used to evaluate crosstalk were not well described. Despite these limitations, and consistent with both these reports, recent results obtained by the authors 39 suggest that the Femiscan electrodes record crosstalk from the hip musculature at contractions levels greater than 25% MVC. With such a result using a proper differential electrode configuration, crosstalk can be expected to be a larger problem with the other commercially available probes that have larger electrode surfaces and monopolar or faux differential configurations.…”
Section: Validity Of Emg Data Recorded From Intravaginal Probessupporting
confidence: 79%
See 1 more Smart Citation
“…Hodges et al 38 reported that crosstalk was not a problem when recording EMG activation from the PFMs using the Periform probe as long as contractions performed by the hip musculature were relatively low amplitude, although they used data from only one participant, hip external rotation was not tested, and the methods used to evaluate crosstalk were not well described. Despite these limitations, and consistent with both these reports, recent results obtained by the authors 39 suggest that the Femiscan electrodes record crosstalk from the hip musculature at contractions levels greater than 25% MVC. With such a result using a proper differential electrode configuration, crosstalk can be expected to be a larger problem with the other commercially available probes that have larger electrode surfaces and monopolar or faux differential configurations.…”
Section: Validity Of Emg Data Recorded From Intravaginal Probessupporting
confidence: 79%
“…With such a result using a proper differential electrode configuration, crosstalk can be expected to be a larger problem with the other commercially available probes that have larger electrode surfaces and monopolar or faux differential configurations. We also showed that the Femiscan probe recorded motion artifact in 29% of EMG signals when women coughed with the probe in situ . Motion artifact contamination has not been studied for other commercially available intravaginal probes.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, the intravaginal probe used may not have these limitations, but these should be considered as important limitations of the use of the intravaginal probes in general. That is because these characteristics of probes might affect its use and the sEMG signal, especially when the intravaginal probe diameter is large (it can change the contractile properties of the PFM due to modification of the muscles length) . Furthermore, the lack of ability to vary the position of the electrode according to the vaginal morphology of each woman is a deficiency of all intravaginal probes available …”
Section: Discussionmentioning
confidence: 99%
“…Regarding the perianal electrodes, they are used by most clinicians during urodynamic evaluations, but it has also important limitations. Because the external anal sphincter is full of motor points, the use of perianal electrodes located on each side of the anal verge may not result in an appropriate differential recording from this muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation